BIG DATA SOURCES AND MECHANISMS FOR THEIR USE IN THE TOURISM SECTOR OF UZBEKISTAN - Najmiddinov Sulton Nurali o‘g‘li (Ecomind Press, 2025)
This article discusses the theoretical and practical aspects of the effective use of Big Data technologies in the tourism sector of Uzbekistan. The article analyzes the importance of Big Data sources available in the Republic of Uzbekistan, including digital tourism platforms, mobile operator data, online booking systems, user activity on social networks, and state statistical databases.
Keywords: Big Data, smart tourism, digital, ecosystem, digital tourism.